A Rare Presentation Of Sepsis Associated Metabolic Encephalopathy With Superadded Uremic Encephalopathy – A Case Report - Pravin, Sachdev Shobha; Azhagarasan, Ashwin Kumar; Gopalakrishnan, Murugan; Chanan, Vishal Ramnath (Journal of Neonatal Surgery, 2025)
Background: Sepsis-associated metabolic encephalopathy is seen in critically ill patients. Uremia worsens sepsis, causing significant cognitive and mental status changes. Objective: To highlight the imaging patterns of septic and uremic encephalopathy. Methods: The patient was brought to the emergency with decreased responsiveness for 2 days. Comprehensive lab evaluations and imaging studies were conducted. Results: Imaging diagnosis was made based on the characteristic brain parenchymal changes in correlation with clinical and lab parameters. On follow up post treatment changes revealed resolution of brain parenchymal changes and improved patient’s clinical status. Discussion: Imaging in septic and metabolic encephalopathy reveals bilateral symmetrical and characteristic changes such as diffuse white matter hyperintensities in brain stem in septic and the Lentiform fork sign in uremic encephalopathy. Conclusion: Clinicians should correlate lab parameters and imaging patterns with altered mental status to optimize treatment.